AD, Volume 14, n° 3, 1989 - Full Issue - journal system, (Africa Development, 1989)
Table of Contents Urbanization and Social Problems in Africa Moriba Touré ................................... 5 La Crise des Finances publiques et la Dénationalisation de l'Etat Bernard Founou-Tchuigo .................. 19 The Human Rights of Africans Joy Mukubwa Hendrickson ..................... 43 Les Limites sectorielles de l'Expérience togolaise de vingt ans de "Planification": l'Agriculture (1966-1985) Ewihn-Liba Pana ......................... 63 Women's Movement and Visions - The Nigeria Labour Congress Women's Wing Kole Ahmed Shettima ...................... 81 Review Article The Icons of Urban and Regional Crisis in South Africa Fassil Demissie ............................ 99 Book Reviews Willem Campschreur & Joost Divendal (Eds.), Culture in Another South Africa Amandina Lihamba ................................ 107 Djillali Liabes, Capital privé et patrons d'Industries en Algérie 1962-1982: Propositions pour l'analyse de couches sociales en Formation Mohamed Lamine Gakou ........................ 111 Publications Received .......................... 113